Penguatan Karakter Religius Melalui Program Pesantren Ramadhan 1445 H Pada Komunitas Teras Baca Nurul Huda Batu Ringgit Kota Mataram Nusa Tenggara Barat: (Strengthening Religious Character Through the Ramadhan 1445 H Islamic Boarding School Program in the Nurul Huda Reading Terrace Community Batu Ringgit Mataram City West Nusa Tenggara) - Hairul Hidayah; Silka Yuanti Draditaswari; Baiq Rofina Arvy; Ilman Paris; Odi Fahrial Azmi (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Islamic religious education in public schools is often said to have little influence on students. Apart from the very limited intensity of study time, namely 2-3 hours of lessons per week, this is also due to the fact that Islamic learning only focuses on basic theoretical knowledge and less on a practical level so that the main goal of Islamic education which touches on the spiritual and social dimensions is difficult to achieve. The Nurul Huda Reading Terrace Community, located in Baturinggit village, Mataram City, NTB, is a forum for informal education for children and teenagers engaged in literacy. Advances in technology and information that have led to shifts in social behavior have given rise to negative behaviors that have led to the apathetic, intolerant, anti-social and hedonistic attitudes of the current generation. This is the basis for the formation of the Ramadhan Islamic boarding school program in the Teras Baca Nurul Huda Baturinggit Mataram comunity, NTB. The Ramadhan Islamic boarding school program has been successfully attended by 60 participants. The aim of this program is to strengthen the religious character of local village children and teenagers who will support the realization of a religious society. The methods of this program include: 1) Preparation; 2) Implementation; and 3) Evaluation and Follow-up. Several activities such as Ramadhan taklim, duarah, donations. Through these activities, religious characters can be strengthened, including love of Allah and His Messenger, independence, courageous, responsible attitudes, a sense of solidarity and mutual respect for each other and an attitude of empathy. The positive response and support of the local community, especially parents and community leaders, guarantees the continuity of this program from the beginning to the end of Ramadan and creates opportunities for its continuation in the future to form a religious, individually and socially pious generation.